Developing a framework of leadership behaviours to facilitate the effective use of lean six sigma in manufacturing: the case of Jordan. - Alnadi, Mohammad (Cranfield University, 2022)
This study aims to explore the leadership behaviours that facilitate the effective use of Lean Six Sigma, whereby organisations and leaders can realise the required behaviours to use the Lean Six Sigma successfully. Leadership is identified as one of the vital factors for the successful implementation of Lean Six Sigma. Thus, this research studies leadership from a behavioural lens. It would be helpful for organisations to get the expected benefits of Lean Six Sigma. An interpretive research philosophy is adopted; reality is constructed through social interaction in which people construct shared meanings and reality. A grounded theory methodology was used to collect and analyse the qualitative data. From that, identifying the required leadership behaviours was based and grounded on the themes that emerged from the data analysis. Twenty-seven interviews were conducted and, through analysing these interviews, thirty-six aspects of leadership behaviours emerged. The researcher made a constant comparison to let the aspects emerge during data analysis. These aspects were given to the participants in the focus group workshop to group them into core categories (themes). Then, ideal position descriptions for each theme were developed to describe what each theme looked like in the most effective and established organisations. The researcher adopted and relied on three sources to identify the possible leadership behaviours to develop the proposed framework. These sources are a focus group workshop, interviews analysis, and the literature. The framework is a series of leadership behaviours that target specific themes. The framework was validated through experts’ judgment from industry. The experts’ feedback was this framework is comprehensive and covers all topics. They believe that adopting these behaviours can lead to achieving the desired goal, which enhances operations efficiency. This research has contributed to facilitating the effective use of Lean Six Sigma by identifying the leadership behaviours required for the successful use of the Lean Six Sigma. Furthermore, it is novel in explaining how the leadership behaviours can support Lean Six Sigma; the themes’ descriptions explain how influence the use of Lean Six Sigma.
Keywords: Lean Six Sigma; leadership practice; implementation; grounded theory methodology; qualitative data; operations efficiency